Global allies comparing US alliances in the 21st century - Wesley, Michael 1968- (Acton, A.C.T. ANU Press, 2017)
The global system of alliances that the United States built after the Second World War underpinned the stability and prosperity of the postwar order. But during the 20th century, the multilateral NATO alliance system in Europe and the bilateral San Francisco alliance system in Asia rarely interacted. This changed in the early 21st century, as US allies came together to fight and stabilise conflicts in the Middle East and Central Asia. This volume presents the first-ever comparative study of US alliances in Europe and Asia from the perspectives of US allies: the challenges, opportunities and shifting dynamics of these fundamental pillars of order. This volume is essential reading for those interested in contemporary and future regional and global security dynamics
Global allies in a changing world / Michael Wesley -- Japan: from passive partner to active ally / HDP Envall -- Germany: a lynchpin ally? / Markus Kaim -- Continuity amidst change: the Korea-United States alliance / Youngshik Bong -- Denmark's fight against irrelevance, or the alliance politics of 'punching above your weight' / Kristian Søby Kristensen & Kristian Knus Larsen -- Crusaders and pragmatists: Australia debates the American alliance / Brendan Taylor & William T Tow -- The challenges and dynamics of alliance policies: Norway, NATO and the high north / Wrenn Yennie Lindgren & Nina Græger -- An ally at the crossroads: Thailand in the US alliance system / Kitti Prasirtsuk -- Poland as an ally / Witold Rodkiewicz
Includes bibliographical references.
Keywords: Balance of power; Alliances; United States -- Foreign relations -- Asia; United States -- Foreign relations -- Europe; United States -- Politics and government -- 21st century